2015
DOI: 10.1186/s13075-015-0622-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA-B*41:02 with Henoch-Schönlein Purpura (IgA Vasculitis) in Spanish individuals irrespective of the HLA-DRB1 status

Abstract: IntroductionA study was conducted to determine whether the human leukocyte antigen (HLA) B alleles are implicated in the susceptibility to Henoch-Schönlein purpura (HSP) in the largest series of Caucasian HSP patients ever assessed for genetic studies.MethodsThe study population was composed of 349 Spanish patients diagnosed with HSP fulfilling the American College of Rheumatology and the Michel et al. classification criteria, and 335 sex and ethnically matched controls. HLA-B phenotypes were determined by seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 20 publications
2
23
2
1
Order By: Relevance
“…However, the genetic component of this type of vasculitis remains poorly understood, as only a few candidate gene studies have been performed to date 4, 5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the genetic component of this type of vasculitis remains poorly understood, as only a few candidate gene studies have been performed to date 4, 5 .…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that they may point to a role of autoimmunity and/or allergy in eBL. HLA‐B*41 has been linked with Henoch–Schönlein purpura among Spaniards (Lopez‐Mejias et al , ); HLA‐B*58 has been linked with severe cutaneous adverse reactions during treatment with allopurinol, particularly in Asians (Hung et al , ); HLA‐DPB1 variants (homozygosity found in 50% of our controls) have been associated with myasthenia gravis (Horiki et al , ), granulomatosis with polyangiitis, immune reactions to beryllium (Potolicchio et al , ), and antigenic response after transplantation (Shaw et al , ). A role of autoimmunity and/or allergy in BL was suggested by findings that the odds of sporadic BL under age 50 years were decreased in those with a history of allergy or asthma in the International Lymphoma consortium (Mbulaiteye et al , ).…”
Section: Discussionmentioning
confidence: 94%
“…These HLA types are believed to influence the immunomodulatory functions of IgA and interleukin 1β. Therefore, HLA molecules can increase one's susceptibility to developing HSP or play a protective role and decrease the likelihood of disease onset [12].…”
Section: Discussionmentioning
confidence: 99%